2020
DOI: 10.1039/d0qi00991a
|View full text |Cite
|
Sign up to set email alerts
|

Induction of immunogenic cell death in cancer cells by a photoactivated platinum(iv) prodrug

Abstract: Photoactivatable prodrug trans,trans,trans-[Pt(N3)2(OH)2(py)2] has a unique mechanism of action, distinguishing it from other platinum drugs due to its immunomodulating properties, which enhance its anticancer efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 47 publications
2
31
0
3
Order By: Relevance
“…This is in strong agreement with previous studies on photoactivation of the mixed amine ligand complex trans , trans , trans -[Pt IV (N 3 ) 2 (OH) 2 (py)­(NH 3 )], for which increased levels of autophagic proteins were detected in cancer cells, implicating autophagy in cell death. Equally, the possible autophagy observed here is consistent with reported chemotherapeutically-stimulated ICD induced in cancer cells by photoactivated Pt1 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in strong agreement with previous studies on photoactivation of the mixed amine ligand complex trans , trans , trans -[Pt IV (N 3 ) 2 (OH) 2 (py)­(NH 3 )], for which increased levels of autophagic proteins were detected in cancer cells, implicating autophagy in cell death. Equally, the possible autophagy observed here is consistent with reported chemotherapeutically-stimulated ICD induced in cancer cells by photoactivated Pt1 …”
Section: Discussionsupporting
confidence: 92%
“…Cytoplasmic vacuoles, traditionally associated with ROS damage and non-apoptotic cell death, were visible even at the lowest concentration (0.25× photoIC 50 , 1.6 μM). These observations are in agreement with the production of N 2 and ROS (perhaps arising from chain reactions of released azidyl radicals) upon irradiation of this class of complexes ,,, and with their cell death mechanisms, likely involving autophagy and immunogenic cell death (ICD) . Interestingly, a large nuclear vacuole surrounded by lipid droplets was observed in a cell treated with 0.5× photoIC 50 (3.2 μM) of Pt2 with irradiation (Figure S19, T14 ).…”
Section: Discussionsupporting
confidence: 82%
“…Separately, Brabec et al 47 reported a photoactivable platinum( iv ) prodrug, 2.7 (designated as complex 1 in the original work) (Fig. 12A).…”
Section: Metal Based Complexes As Icd Inducersmentioning
confidence: 99%
“…This study thus provides support for the emerging impression that autophagy may be playing an essential role in promoting the immunogenic release of ATP from dying cells. Unfortunately, in vivo studies to support the putative benefit of this novel photoactivable approach to ICD induction were not included in the original report 47 or, apparently, been the subject of follow-up efforts.…”
Section: Metal Based Complexes As Icd Inducersmentioning
confidence: 99%
“…Another strategy employed by Pt drugs, namely, immunogenic cell death induced by photoactive Pt complexes, might be important for antimetastatic activity [76].…”
Section: Metallodrugs Against Migration and Metastatic Processesmentioning
confidence: 99%